The Relationship Between Parenting and Feeding Patterns On The Incidence Of Stunting - Rita Aprianti (Sean Institute, 2023)
Stunting is a significant highlight in Indonesia because it is continually rising. Factor pattern of bad parenting and inappropriate infant feeding is a risk cause of stunting. The purpose of this research is to analyze the connection pattern parenting and patterns of provision of food to the incidence of stunting in infants. This research is a quantitative study with a cross-sectional design. This research was conducted in the Health Center Cipadung working area in January- March 2022. The research population is mothers with toddlers. A sample of 84 respondents was taken randomly. The instruments used are a measuring tool height and a questionnaire. Data analysis used the chi-square test. The research showed that pattern parenting (p=0.045 and POR=2.9) and pattern feeding (p=0.014 and POR=3.3) are associated with stunting. Parenting and patterns of feeding are related to the incidence of stunting. Good maternal parenting can prevent children from experiencing stunting and feeding; if mothers provide the right food for their children, then children can be spared from stunting.